Fundamental of Entrepreneurship ENT300 : Loveberts / Fatin Najwa Mohammed Azamri ... [et al.] - Mohammed Azamri, Fatin Najwa; Wan Hady, Wan Nur Atikah; Erick, Michelle (2019)
The name of our company is Loveberts. The form of our company is a partnership business which consist of three group members. Regarding to our partnership agreement, we will contribute RM30,000 for our business’ capital. The business will estimate to commence on 19th January, 2019 and we hope that our business will give benefits to the community and expand our business to the international market. The vision of our company is “we will offer high quality products and services to the customers on order to gain profits so that we could expand our business in Malaysia”, in order to achieve our vision, we have to complete our mission “it is our duty to make the most delicious sticky rice cakes, have the originality of idea and to serve efficient food services”. Our objective for doing this business is to gain more profits from the Mitarashi Dango that we have produce and maintain our sales in every year. Loveberts provides a delicious Mitarashi Dango which can give a satisfaction to all of our customers.